Internalization of isolated functional mitochondria: involvement of macropinocytosis. Issue 8 (9th June 2014) - Kitani, Tomoya; Kami, Daisuke; Matoba, Satoaki; Gojo, Satoshi
Abstract In eukaryotic cells, mitochondrial dysfunction is associated with a variety of human diseases. Delivery of exogenous functional mitochondria into damaged cells has been proposed as a mechanism of cell transplant and physiological repair for damaged tissue. We here demonstrated that isolated mitochondria can be transferred into homogeneic and xenogeneic cells by simple co‐incubation using genetically labelled mitochondria, and elucidated the mechanism and the effect of direct mitochondrial transfer. Intracellular localization of exogenous mitochondria was confirmed by PCR, real‐time PCR, live fluorescence imaging, three‐dimensional reconstruction imaging, continuous time‐lapse microscopic observation, flow cytometric analysis and immunoelectron microscopy. Isolated homogeneic mitochondria were transferred into human uterine endometrial gland‐derived mesenchymal cells in a dose‐dependent manner. Moreover, mitochondrial transfer rescued the mitochondrial respiratory function and improved the cellular viability in mitochondrial DNA‐depleted cells and these effects lasted several days. Finally, we discovered that mitochondrial internalization involves macropinocytosis. In conclusion, these data support direct transfer of exogenous mitochondria as a promising approach for the treatment of various diseases.